The welfare economics of adaptive preferences - Carl Christian von Weizsäcker (Max Planck Institute for Research on Collective Goods, 2005)
In this paper I demonstrate that a reasonable welfare theoretic concept of progress can be made consistent with the assumption of endogenously changing preferences as long as these preference changes correspond to the pattern of adaptive preferences. The main theorem of the paper shows that under certain additional conditions adaptive preferences imply the existence of a complete pre-ordering of the consumption space in terms of improvement paths which allow endogenous preference changes. It is then shown that welfare economics of improvement paths is also possible with interpersonal influences on preferences. A conjecture is developed that results of recent empirical and experimental research into human economic behaviour corroborate the hypothesis of adaptive preferences.
Keywords: 330; Welfare Economics; Endogenous Preferences; Adaptive Preferences; Interpersonal Influences on Preferences; Improvement Paths; Bounded Rationality